2023
DOI: 10.1002/cphc.202300370
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Theory Calculations for Multiple Conformers Explaining the Regio‐ and Stereoselectivity of Ti‐Catalyzed Hydroaminoalkylation Reactions

Niklas Thoben,
Tobias Kaper,
Simon de Graaff
et al.

Abstract: Hybrid Density Functional Theory (DFT) calculations for multiple conformers of the insertion reactions of a methylenecyclopropane into the Ti−C bond of two differently α‐substituted titanaaziridines explain the experimentally observed differences in regioselectivity between catalytic hydroaminoalkylation reactions of methylenecyclopropanes with α‐phenyl‐substituted secondary amines and corresponding stoichiometric reactions of a methylenecyclopropane with titanaaziridines, which can only be achieved with α‐uns… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 104 publications
1
1
0
Order By: Relevance
“…10 The relative configuration of 29 was elucidated by single-crystal X-ray diffraction analysis of the corresponding hydrochloride 29·HCl (Figure 4 ), 11 and it was found that 29 has the expected cis -orientation of the dimethylaminomethyl substituent and the cyclopropane hydrogen atoms. This finding is in good agreement with closely related DFT-calculations, 16 which have already shown that hydroaminoalkylation of a corresponding methylenecyclopropane with secondary amines can only occur from its convex side.…”
Section: Table 1 Ti-catalyzed Hydroaminoalkylation Reac...supporting
confidence: 92%
“…10 The relative configuration of 29 was elucidated by single-crystal X-ray diffraction analysis of the corresponding hydrochloride 29·HCl (Figure 4 ), 11 and it was found that 29 has the expected cis -orientation of the dimethylaminomethyl substituent and the cyclopropane hydrogen atoms. This finding is in good agreement with closely related DFT-calculations, 16 which have already shown that hydroaminoalkylation of a corresponding methylenecyclopropane with secondary amines can only occur from its convex side.…”
Section: Table 1 Ti-catalyzed Hydroaminoalkylation Reac...supporting
confidence: 92%
“…Areas of Applications : DFT has found numerous applications in chemistry and materials science by calculating the electronic ground-state properties of various systems. , In solid-state calculations, the LDA is still commonly used along with plane-wave basis sets, as an electron-gas approach is more appropriate for electrons delocalized through an infinite solid. However, in calculations involving molecular systems, more accurate long-range corrected XC functionals ( e.g.…”
Section: Existing Theoretical and Computational Methods And Their Limitsmentioning
confidence: 99%